Women's Empowerment Trough Barbie (2023) - Ramadhan, Chintya Ayu (Universitas Negeri Surabaya, 2024)
This study aims to analyze women empowerment in Barbie (2023) film directed by Greta Gerwig, with a special focus on the depiction of female characters and exploring the theme of empowerment within the film's narrative framework. Using the concept of women empowerment by Rowlands (1997) as a basis analysis, this study's main aim is to gain an in-depth understanding of how women's empowerment is depicted in films and its impact on male characters. This study also aims to explore the concept of women's empowerment as a process that enables women to control their lives, make choices, and enforce their rights.